ANALISIS PERTUMBUHAN ORGANISASI KEPEMUDAAN DAN IMPLIKASINYA TERHADAP KERUKUNAN ANTAR SUKU DI KOTA SAMARINDA - Saputra, Chendra Adi (Magister Administrasi Publik FISIP Universitas Mulawarman, 2022)
This article discusses the description of the growth of tribal-based youth organizations and the dynamics of the implications of their presence on inter-ethnic harmony in Samarinda City. A qualitative approach is used as a research method. The research data were obtained from observations, interviews, literature studies and documentation which were analyzed using a qualitative data analysis model. The research findings show an increase in terms of quantity and is in the infant period and childhood phase (Go-Go). The presence of tribal-based youth organizations has real implications for the creation of inter-tribal harmony through the dynamics and behavior of youth organizations which are reflected in positive activities that support the creation of harmony such as peace ambassador activities, sirapeang, fundraising, and joint sports competitions.Keyword: organizational growth, implications, youth, ethnicity, harmony